2023
DOI: 10.1002/ijgo.15189
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pelvic floor disorders on sexuality in women

Juan Miguel Martínez‐Galiano,
Rocío Adriana Peinado‐Molina,
Sergio Martínez‐Vazquez
et al.

Abstract: ObjectiveTo determine the association between different pelvic floor disorders and the presence of sexual dysfunction in women.MethodAn observational study of non‐pregnant women was carried out in Spain in 2021 and 2022. To assess the presence of pelvic floor problems, the Pelvic Floor Distress Inventory (PFDI‐20) was used, consisting of the subscales Pelvic Organ Prolapse Distress Inventory‐6 (POPDI‐6; prolapse symptoms), Colorectal‐Anal Distress Inventory (CRADI‐8; colorectal symptoms), and Urinary Distress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…In our sample, the sexual dysfunction was found to be remarkably higher among patients, with every domain of sexual function being impaired compared to the control group ( Table 5 ). Martínez-Galiano et al (2023) [ 40 ] found a prevalence of 28.6% for sexual dysfunction in a sample of 1008 women. Furthermore, their study showed that women with sexual dysfunction had significantly higher mean scores in the UDI-6, POPDI-6, and CRADI-8 sub-scales of the PFDI-20 than those without sexual dysfunction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our sample, the sexual dysfunction was found to be remarkably higher among patients, with every domain of sexual function being impaired compared to the control group ( Table 5 ). Martínez-Galiano et al (2023) [ 40 ] found a prevalence of 28.6% for sexual dysfunction in a sample of 1008 women. Furthermore, their study showed that women with sexual dysfunction had significantly higher mean scores in the UDI-6, POPDI-6, and CRADI-8 sub-scales of the PFDI-20 than those without sexual dysfunction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Martínez-Galiano et al (2023) [ 40 ] found a prevalence of 28.6% for sexual dysfunction in a sample of 1008 women. Furthermore, their study showed that women with sexual dysfunction had significantly higher mean scores in the UDI-6, POPDI-6, and CRADI-8 sub-scales of the PFDI-20 than those without sexual dysfunction [ 40 ].…”
Section: Discussionmentioning
confidence: 99%